Associations of Childhood Maltreatment and Attachment Styles with Romantic Breakup Grief Severity: The Role of Emotional Suppression. Issue 13 (July 2022) - Heshmati, Rasoul; Zemestani, Mehdi; Vujanovic, Anka
Childhood maltreatment (CM) and insecure attachment styles may partly explain grief severity following romantic breakup. Empirical studies examining the factors that could possibly explain this association, however, remain sparse. The present study tested whether the relations among CM, attachment styles, and romantic breakup grief severity could be explained by emotional suppression in Iranian college students. In a cross-sectional study, 239 Iranian college students (ages 18–45; M = 24.11, SD = 15.29; 50.6% women) with a recent romantic breakup experience were recruited from University of Tabriz. Participants completed a diagnostic interview and self-report battery, including the Persian version of the Child Abuse Self-Reported Scale, Revised Adult Attachment Scale, Romantic Breakup Grief Inventory, and Weinberger Adjustment Inventory. Structural equation modeling was used to empirically explore the relations among variables. Results indicated that those who reported higher levels of CM also reported higher levels of romantic breakup grief. Attachment closeness showed a significant negative and direct effect on romantic breakup grief severity. However, attachment anxiety was positively associated with greater levels of romantic breakup grief. Bootstrapping results showed that CM might affect romantic breakup grief severity via emotional suppression. Furthermore, attachment closeness and attachment anxiety exerted indirect effects on romantic breakup grief severity through emotional suppression. Clinical and empirical implications are discussed.